Nursing Care Of Mr.P With Endocrine Systemdisorder: Diabetes Mellitus Post Amputation Pedis Sinistra 2 Th Days In The Sofa Ward In PKU Muhammadiyah Surakarta Hospital - Yulianasari, Yulianasari (2012)
Background: Wound amputation in DM is the Rapture/cutting/disposal of some members of the body/limb injuries caused some blackish red and some of the tissues are dead and thereby make it stinks because of serious chronic diseases caused by hereditary or environmental factor that is marked by an increase on the levels of glucose in the blood or hyperglycemic (ha ve a levels fasting blood sugar > 126 mg/dL and on tests on a while> 200 mg/dL). Objective: To know the action of orphanage nursing in patients with DM post Amputate pedis sinistra includes the study, diagnose intervention, implementation and evaluation. Results: At the time of the assessment of the data obtained pedis pain on the left who are post amputation wound. Diagnosis of acute pain that arises is,the risk of infection, impaired compliance activity, body image disturbance. In the action plan already in the theory. Implementation of measures already implemented denagn good fit theory. After doing the action of nursing for 3 times in a day, his pain has been reduced from 6 to 4 scale, there are no signs of infection, the activities of the patient are still assisted by the families, patients can already receive his condition to live with one leg. Conclusion: Co-operation between the health team and patient/family is indispensable to the success of the orphanage of nursing on patients. In general, the intervention can be done well, it is supported by a cooperative of the pa tient, patient wants to do therapy that is given and adhere well for example: patient wants to do therapy while nursing wounds.